A Spatial Analysis of Green Technological Innovation and Environmental Sustainability: Exploring the Role of Globalization (Journal of Asian Development Studies, 2025)
The current study investigates the spatial spillover effect of green technological innovations (GI) on environmental sustainability in the presence of globalization (GB). Environmental sustainability is measured using an index called Environmental Health (EH), which reflects environmental quality based on four indicators: air quality, sanitation, heavy metals, and waste management. The study employs spatial methods to analyze the direct, indirect, and total effects of green technological innovation (GI) and globalization (GB) on environmental sustainability across 60 global economies from 1990 to 2022. To investigate the moderating role of globalization (GB), fixed- and random-effects models, structural equation models, and spatial econometric models are estimated. The results show that globalization (GB) has dual moderating effects: while it directly and indirectly (spatially) aggravates environmental pressures, its interaction with green technological innovations (GI) improves environmental sustainability. Similarly, economic development (ED) is found to increase environmental degradation, while urbanization (UR) shows adverse direct spillover effects but improves environmental sustainability at the global scale. The study provides significant policy insights, highlighting the need to understand the repercussions of globalization (GB) and to invest in green technological innovations (GI) to foster a sustainable global environment.